Intertextual Folklore in Animated Comics As a Learning Model of Appreciative Reading - Setiartin, T (KnE Social Sciences, 2018)
This study emphasized aesthetic-receptive and critical-creative activities in the form of a creative process of appreciative reading. The learning of appreciative reading in class XI of Vocational High School (SMK) was considered to be less than optimal by many circles. The main problem was that they were less interested in appreciative reading and more interested in product creation in learning. Aesthetic-receptive and critical-creative reading may develop the students’ product creativity from their learning results. This research used a qualitative-quantitative subsequential exploratory design with a pretest-posttest matching pattern. Analysis of the class using a limited test, broad test, and validation test. Keywords: appreciative reading, comics, intertextual